Business based smart operations and digital supply chain performance - Fernando, Yudi; Mergeresa, Fineke; Wahyuni-Td, Ika Sari; Gui, Anderes; Ikhsan, Ridho Bramulya; Prabowo, Hartiwi (Institute of Electrical and Electronics Engineers Inc., 2021)
This study examines the relationship between business based smart operations and digital supply chain performance. The mediating role of Industry 4.0 related technological capability has been included in the research model. Data were collected from the manufacturing industry in Indonesia. The PLS-SEM was utilized to test the proposed hypotheses. The results found that business based smart operations have opened the opportunity to improve productivity and effective coordination among supply chain networks. The automation in the business operation to support production and logistics activities needs a capable workforce and sufficient infrastructure. The manufacturing industry needs to connect the smart business operation with cyber-physical systems, the Internet of things and cloud computing.